The characteristics of success : biographical and behavioural determinants in the selection of Life Insurance Agents. - Goh, Andrew. (2008)
Making choices remains at the core of Personnel Selection. It is not possible for any organization to hire every applicant and later evaluate whether to retain or dismiss them. Hence, selection decisions are needed up-front and these are basically predictions (Milkovich & Boudrea, 1991). As Smith (1994) indicated, the essence of selection is to identify those measures that predict job success or work performance. An important and established tenet in this field is that past behaviour is the most effective predictor of future behaviour. Recruiting and selecting the right candidates is as important for the life insurance industry as for many others. With a disappointing 15% retention rate record over a five-year time frame, this industry has allocated much time, money and effort to ascertain the characteristics (predictors) of success so as to reduce turnover and high costs in the hiring process. There is also concern about the gap existing between academia and practice. Research findings are not being put into use and practitioners may be utilising methods that are known not to be reliable or valid. One proven tool or technique in current use involves biodata (bibliographical or background personal history data). The Life Insurance Marketing and Research Association (LIMRA) has served the industry for over 70 years. They developed a selection tool (the AIB - Aptitude Index Battery) which originally consisted of two parts (a) biodata and (b) psychological factors. The latter was later discarded because of low reliability. In its present form, the AIB comprises only the former.